Arah Kebijakan Dalam Penataan Kawasan Sempadan Rel Kereta Api di Kecamatan Labuhan Ratu Berdasarkan Rencana Tata Ruang Wilayah (RTRW) Kota Bandar Lampung Tahun 2021-2041 - Panti Wahyuningsih; Rahayu Sulistyorini; Bambang Utoyo Sutiyoso (Administratio, 2023)
The research conducted aims to implement policies regarding the arrangement of railroad border areas, especially settlements located in Labuhan Ratu District based on Regional Regulation Number 4 of 2021-2041 concerning the Regional Spatial Plan (RTRW) of Bandar Lampung City. The research method used is descriptive qualitative. The research was conducted along the railroad tracks in Labuhan Ratu Subdistrict. The data collection stage was carried out using field observation methods and interviews with resource persons both local residents and related parties. The results showed that the existence of settlements has become a problem in itself both for the safety of train travel and the security and quality of life of the community. This happens because the existing policies have not been implemented optimally, so there is a need for alternative policies in structuring residential areas located on the railroad border. his research provides a theoretical contribution in making alternative policy directions in structuring residential areas on the railroad border, especially in Labuhan Ratu District, Bandar Lampung City.